Assessment of growth, genotoxic responses and expression of stress related genes in the Pacific oyster Crassostrea gigas following chronic exposure to ionizing radiation. Issue 2 (30th June 2015) - Devos, Alexandre; Dallas, Lorna J.; Voiseux, Claire; Lecomte-Pradines, Catherine; Jha, Awadhesh N.; Fiévet, Bruno
Highlights: Oyster were chronically exposed to ionizing radiation. Survival and growth were not impaired at the exposure levels tested. Transcriptional expression of selected stress genes was not significantly changed. DNA damage was observed with no apparent detriment at the physiological level. Abstract: Marine organisms are exposed to low doses of anthropogenic contaminants during their entire life. Authorized amounts of radionuclides are discharged in the Channel by nuclear facilities. The Pacific oyster was used to investigate the potential impact of chronic exposure to ionizing radiation. Though we exposed larvae and spat for two weeks to much higher concentrations than those encountered near nuclear facilities, oyster growth and expression of 9 selected stress genes were not significantly changed. To determine potential DNA damage, 2 year old oysters were exposed for two weeks to tritiated water. The comet assay was used to evaluate the level of DNA strand breaks in haemocytes, whilst the 'clearance rate' was used as a measure of physiological effects. Whilst other parameters did not alter, DNA damage significantly increased. Our results highlight the significance of the observed DNA damage and their potential consequences at higher levels of biological organization.